Commercially Available Toothpaste in India - Debasruti Naik1, Motirmoy Giri2, Ramesh Nagarajappa3, Sudipta Sahu4, Kajal Kiran Sahu5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Majority of us spend very little time or else may be no time while choosing the right as well as the besttoothpaste for our mouth because good oral health should be the prime importance. Everyone wishes to havean impressive personality, and for that attractive appearance, a beautiful smile is always required. Withoutproper oral care an attractive smile cannot be achieved. Toothpaste is not only a bathroom requirement; itis the most important material for maintaining good oral hygiene. All toothpaste that are available in themarket commercially today is formulated and designed to clean our teeth and help in maintaining good oralhygiene, all the products do notachieve that need equally. Some of the commercial toothpaste products havethe potential to damage our teeth, while others simply don’t provide enough protection to our teeth as perrequirement. This article highlights the toothpaste available in the Indian market so that one should be ableto select the right balance of toothpaste according to his/her oral health needs.